Horizontal-vertical illusion in mental imagery: quantitative evidence - Blanuša, Jelena; Zdravković, Sunčica (Frontiers in Human Neuroscience, 2015)
The present study had two main goals: (1) to investigate the difference between perception and mental imagery using a visual illusion as a stimulus; (2) to inspect gender related differences in perception and imagery. Our main hypothesis that there would be no differences between perception and mental imagery, was motivated by previous neuroimaging data. Unlike these neuroimaging studies that demonstrate great similarity between the two processes, results obtained in behavioral studies have not always been consistent. We assumed that this inconsistency was a consequence of methodological irregularities. Hence, we explored the two processes with a modified behavioral procedure. The additional exploration of gender differences was motivated by the discrepancy between our findings and the existing literature. In two experiments, participants estimated the lines constituting the horizontal-vertical illusion, either in perception or imagery task. Results confirmed that there was no significant difference between perception and imagery: the illusion was equally strong in both tasks. In the second experiment, an additional factor was tested, stimulus size. The results showed that, although there was no significant difference in illusion strength, there was a gender difference in the size of mental image for medium and large stimuli. While male subjects performed equally in the two tasks, female subjects tended to underestimate size in the imagery task. This tendency intensified as the stimulus size increased. Our results not only inform us about the status of illusions in imagery but also offer some answers about the spatial nature of mental representations. We hope that such precise measurements of mental representation might provide better understanding of reasoning that uses mental images.